Effects of glucose and trehalose on tris-citric acid-egg yolk-fructose diluents for semen cryopreservation in goat - Kamal, Md Mostofa; Alam, Md Emtiaj; Das, Sunny Kumar; Yeasmin, Most Shorifa; Ahmed, Soshe; Rahman, Mst Afroza; Das, Dipak Kumar; Gofur, Md Royhan; Masum, Md Abdul (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: This study aimed to examine the impacts of the wide range of concentrations of glucose and trehalose on the tris-citric acid-egg yolk-fructose (TCEF) extenders for cryopreservation of goat semen. Materials and Methods: The sperm sample was pooled, washed, and diluted in control (TCEF without glucose and trehalose), TCEF + glucose (75, 150, 450, and 900 mm), and TCEF + trehalose (75, 150, 450, and 900 mm). After equilibrations, the semen straws were frozen under LN2 in the LN2 tank. After LN2 storage, the straws were thawed at 37°C for 30 seconds. The sperm parameters of all study groups were checked after equilibration and freezing. Results: After equilibration, the progressive motility (PM), total motility (TM), and viability of sperm in G-75, G-150, G-450, T-75, T-150, and T-450 were not significantly different (p < 0.05) from those in control. After cryopreservation and thawing, the PM, TM, and plasma membrane integrity (PMI) of T-150 were significantly higher (p < 0.05) than in control, G-75, G-900, T-75, and T-900. The viability of sperm in T-150 was substantially higher (p < 0.05) than in the control, whereas there was no significant difference among the control, G-75, G-900, T-75, and T-900. However, the acrosome integrity (AI) of sperm in G-900 was significantly decreased (p < 0.05) compared to the control, G-75, G-150, G-450, T-75, T-150, and T-450. Conclusion: According to the findings, the supplementation of 150 mm trehalose in the TCEF diluent was more efficient for sperm cryopreservation in the buck as reflected by PM, TM, viability, PMI, and AI. J. Adv. Vet. Anim. Res., 10(2): 169–177, June 2023 http://doi.org/10.5455/javar.2023.j666